Cobalt nickel nitride coated by a thin carbon layer anchoring on nitrogen-doped carbon nanotube anodes for high-performance lithium-ion batteries. Issue 40 (8th October 2018) - Zou, Rujia; Xu, Mingdong; He, Shu-Ang; Han, Xiaoyu; Lin, Runjia; Cui, Zhe; He, Guanjie; Brett, Daniel J. L.; Guo, Zheng Xiao; Hu, Junqing; Parkin, Ivan P.
Abstract : We report a new material and a structural configuration for lithium-ion batteries consisting of cobalt nickel nitride coated by a thin carbon layer anchoring on nitrogen-doped carbon nanotubes. The anode delivers excellent lithium storage properties. Abstract : Cobalt nickel nitrides coated by a thin carbon layer anchoring on nitrogen-doped carbon nanotubes, named NiCo2 N@C–NCNT nanocomposites, were obtained by a facile fabrication method. The work reveals that the NiCo2 N structures possess extensive Li + channels and high electrical conductivity for the rapid electron/ion transfer in lithium-ion batteries (LIBs). These materials were applied as anodes for the first time, and a nanobattery was constructed and examined using a transmission electron microscope (TEM) to directly verify the in situ structural evolution during lithiation/delithiation processes. The results show a small dimensional expansion of the NiCo2 N@C–NCNT nanocomposites during the lithiation process; this is due to the disciform expansion of the lithiated NiCo2 N nanoparticles which cover the surface of the NCNTs. It was found that some of the lithiated NiCo2 N nanoparticles moved along the surface of the NCNTs and entered the NCNTs – thus acting to 'protect' themselves. Moreover, electrodes composed of interconnected NCNTs alleviate the volumetric expansion of NiCo2 N@C–NCNT nanocomposites. The NiCo2 N@C–NCNT nanocomposite electrode exhibits excellent lithium storage properties in electrochemical tests in coin cell configurations. This material synthesis route and 'self-protection' mechanism provide the basis of a design strategy for developing effective electrode materials in LIBs and a broader sphere of metal-ion batteries.